God, justice, and society aspects of law and legality in the Bible - Burnside, Jonathan P. (Jonathan Patrick) (New York ; Oxford : Oxford University Press, 2011)
What is the real meaning of 'an eye for an eye and a tooth for a tooth'? Where did the idea for the 'Jubilee 2000' and 'Drop the Debt' campaigns come from? Here, Burnside looks at aspects of law and legality in the Bible, from the patriarchal narratives in the Hebrew Bible through to the trials of Jesus in the New Testament.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Jan. 12, 2011).
Keywords: Bible and law; Law (Theology) -- Biblical teaching